A framework of subjective financial well-being among university students in Malaysia - Low, Kah Choon (College of Law, Government and International Studies, Universiti Utara Malaysia, 2020)
Living within one’s means is the practice that ensures that a person can survive and able to support their living. However, young working adults in Malaysia struggle to make ends meet for them to cover their basic needs.This problem calls the attention of personal finance management role in improving one’s financial well-being. University students are characterised as emerging adults, which their life stage is between adolescents and adults. This emerging stage plays as the transition stage for them before they become a working adult that requires them to manage their own personal finance and not depending on the financial support from their parents. People in a similar financial situation could perceive their financial well-being differently. Due to the specific characteristics of the university students and differences in perceiving their financial well-being, this inspires researcher to investigate the factors (financial literacy and financial behaviour), based on Theory of Planned Behaviour and Happiness Framework, that contribute to financial well-being. Hence, this paper attempted to (1) conceptualise financial well-being in a subjective approach to capture the students’ financial wellbeing situation in a more holistic picture and (2) discuss the relationships among the factors contributing to the subjective financial well-being of the university students. It is significant because the concept is defined in varies forms in past studies and the relationships among the factors require further clarifications.